2003
DOI: 10.1046/j.1365-294x.2003.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal divergence of common frog (Rana temporaria) life history traits by natural selection: evidence from a comparison of molecular and quantitative genetic data

Abstract: The relative roles of natural selection and direct environmental induction, as well as of natural selection and genetic drift, in creating clinal latitudinal variation in quantitative traits have seldom been assessed in vertebrates. To address these issues, we compared molecular and quantitative genetic differentiation between six common frog (Rana temporaria) populations along an approximately 1600 km long latitudinal gradient across Scandinavia. The degree of population differentiation (QST approximately 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
240
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(264 citation statements)
references
References 88 publications
(151 reference statements)
17
240
6
1
Order By: Relevance
“…Common garden experiments conducted in Scandinavia reveal a genetic basis to geographical variation in the developmental rates of R. temporaria tadpoles (12). Evidence that geographical variation in development rates of this species has arisen via natural selection comes from the observation that divergence in quantitative traits relating to development rates exceeds that at neutral genetic loci (13). The statistical test that we used to assess the extent of local adaptation of spawning date to winter temperatures in Britain is based on the quantitative genetics model developed below.…”
mentioning
confidence: 99%
“…Common garden experiments conducted in Scandinavia reveal a genetic basis to geographical variation in the developmental rates of R. temporaria tadpoles (12). Evidence that geographical variation in development rates of this species has arisen via natural selection comes from the observation that divergence in quantitative traits relating to development rates exceeds that at neutral genetic loci (13). The statistical test that we used to assess the extent of local adaptation of spawning date to winter temperatures in Britain is based on the quantitative genetics model developed below.…”
mentioning
confidence: 99%
“…These experimental sampling designs are similar to those used in several studies estimating Q ST o , with total number of individuals at 1000 (e.g., Spitze 1993;Lynch et al 1999;Palo et al 2003;Morgan et al 2005). Often, however, the total number of individuals used to infer Q ST is ,1000 (e.g., Bonnin et al 1996;Petit et al 2001;Steinger et al 2002).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…If the inclusion of nonadditive genetic variance causes a downward bias in Q ST , past studies may have underestimated differences in life-history traits relative to morphological traits. Indeed, previous studies by Koskinen et al (2002) and Palo et al (2003) that also used additive genetic variance to estimate Q ST found extreme divergence in most of the quantitative life-history traits they studied, relative to F ST of neutral loci. Furthermore, a recent metaanalysis (e.g., Leinonen et al 2008) that includes more studies using additive genetic variance to estimate Q ST found no difference between life-history and morphological traits.…”
Section: Discussionmentioning
confidence: 97%